Analisis Reduplikasi Pada Karangan Deskripsi Siswa Kelas VII SMP Negeri 2 Gatak Sukoharjo - Susilowati, Anik; , Dr. Yakub Nasuha,M.Hum (2017)
The purpose of the research to (1) Identify the forms of reduplication contained in the student descriptive essay grade VII SMP Negeri 2 Gatak, (2) Describes the meaning of reduplication contained in the student descriptive essay grade VII SMP Negeri 2 Gatak. Type of the research is qualitative descriptive. Data source in this research is student descriptive essay grade VII H and F SMP Negeri 2 Gatak Sukoharjo. Data collection techniques in this research are read and note techniques. Data analyze techniques use the technique BUL with agih method. The result of this research are (1) Forms of reduplication contained in the student descriptive essay there are four, (a) repetition all over, (b) repetition in part, (c) repetition affixed, and (d) repetition with variation of phoneme. Majority data reduplication is found repetition with affixed. (2) The meaning of reduplication contained in the student descriptive essay are 'much', 'unconditional', 'deeds done over and over again', 'each other', 'character', 'circumstances or situation', 'related things', 'the highest level or superlative', 'intensity of feeling', and 'resembles'. However the meaning of reduplication often found are the meaning 'much' and the meaning 'character'.